Health-care distribution of patients with genitourinary birth defects in Colombia: a spatial analysis of registered cases - Jessica Santander; Andrés Gutiérrez; Marcela Pérez-Sosa; María P. Donoso; Nicolas Fernandez (Urología Colombiana)
Introduction: Genitourinary birth defects are reported to be present in approximately 10-30% of all newborns. Timely treatments may reduce complications that contribute to increased infant morbimortality. Understanding the distribution of health access is essential for the design of health interventions and resource distribution. Objective: We aim to evaluate the geographical distribution of the healthcare access to subspecialized medical care of patients with genitourinary birth defects in Colombia. Method: We reviewed data collected between January 2015 and December 2019 in the Individual Health Records System (RIPS). All registered patients diagnosed with renal malformations, male genital malformations, and exstrophy-epispadias complex as well as all registered live births were included. Cluster detection was performed using a Poisson model with SaTScan v9.6. To visualize the results, the clusters were projected in a Google Earth map. Results: Between January 2015 and December 2019 a total of 26,726 patients with renal malformations, 19,149 patients with genital malformations, and 494 patients with exstrophy-epispadias complex in the outpatient clinic were assessed in Colombian territory. A space-time analysis identified one cluster with high provided health care concentration seen in the center of the country for renal and genital malformations. Meanwhile, northern regions close to the coast were identified as clusters with low rates of provided care regions. For cases with exstrophy-epispadias complex, regions in the north had lower registered assessments compared to the center of the country. Conclusion: Patients with genitourinary malformations have inequitable access to specialized health care which can delay surgical management and impact long-term outcomes that increase disability.